Understanding plagiarism (Journal of Patan Academy of Health Sciences, 2024)
Plagiarism is copying ideas, thoughts, and others’ work and presenting them as one’s own without acknowledgment which is akin to intellectual property theft. A meta-analysis found that the researchersadmitting to plagiarism or other forms of scientific misconduct is at 2.9 percent. While people are hesitant to admit themselves indulged in plagiarism and other scientific misconduct, they are upfront in pointing out at others. This has been shown in one of the studies where 1.7 percent have admitted to plagiarism while the witness to plagiarism is at 30 percent. The next most prevalent form of plagiarism is stealing others’ ideas and passing them on as their own without acknowledging them. A meta-analysis revealed that 15.5% of researchers witnessed others who had committed at least one Research Misconduct, while 39.7% were aware of others who had used at least one Questionable Research Practice.2Plagiarism is a pervasive issue that has plagued the scientific community and the academic world for a long time. On the one hand, it stains the integrity of the researcher while on the other, it renders the credibility of the institutions questionable. Ethical bodies and scientific journals play a pivotal role in identifying, preventing, and addressing issues of plagiarism to preserve the trust and faith of the scientific community.